Circ-PDE1C/miR-766-3p/SGTB axis regulates the IL-1β-induced apoptosis, inflammation and oxidative stress in human chondrocytes - Lixia Gao; Tao He; Qingkui Hu; Yan Ma (Advances in Rheumatology)
Abstract Background Osteoarthritis (OA) is a common degenerative joint disease. Circular RNA Phosphodiesterase 1 C (circ-PDE1C, hsa_circ_0134111) has participated in the IL-1β-induced chondrocyte damages. The objective of our study was to explore the molecular mechanism of circ-PDE1C. Methods Circ-PDE1C, microRNA-766-3p (miR-766-3p) or Small Glutamine Rich Tetratricopeptide Repeat Co-Chaperone Beta (SGTB) expression was determined using reverse transcription-quantitative polymerase chain reaction (RT-qPCR). Cell counting kit-8 (CCK-8) assay and flow cytometry were used to analyze proliferation and apoptosis, respectively. Western blotting assay was performed for protein detection. The inflammatory cytokines were measured by Enzyme-linked immunosorbent assay (ELISA). Oxidative stress was assessed by commercial kits. Target analysis was conducted by dual-luciferase reporter assay and RNA immunoprecipitation (RIP) assay. Results Circ-PDE1C was abnormally overexpressed in OA tissues and IL-1β-exposed chondrocytes. Downregulation of circ-PDE1C alleviated the IL-1β-induced cell apoptosis, inflammation, extracellular matrix degradation and oxidative stress. Circ-PDE1C could interact with miR-766-3p to serve as miRNA sponge. The function of si-circ-PDE1C was attributed to the inhibition of miR-766-3p. Additionally, miR-766-3p directly targeted the 3’UTR of SGTB. The miR-766-3p upregulation impeded the IL-1β-triggered cell damages through reducing the level of SGTB. Moreover, SGTB expression was regulated by circ-PDE1C via binding to miR-766-3p in IL-1β-induced chondrocytes. Conclusion Altogether, circ-PDE1C enhanced the IL-1β-induced dysfunction in chondrocytes via upregulating SGTB by targeting miR-766-3p.